2014
DOI: 10.3233/jpd-140364
|View full text |Cite
|
Sign up to set email alerts
|

Motor and Cognitive Advantages Persist 12 Months After Exenatide Exposure in Parkinson’s Disease

Abstract: Abstract. Background:Data from an open label randomised controlled trial have suggested possible advantages on both motor and non-motor measures in patients with Parkinson's disease following 12 months exposure to exenatide. Objective: Continued follow up of these same patients was performed to investigate whether these possible advantages persisted in the prolonged absence of this medication. Methods: All participants from an open label, randomised controlled trial of exenatide as a treatment for Parkinson's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
152
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 228 publications
(157 citation statements)
references
References 19 publications
5
152
0
Order By: Relevance
“…In addition to hypoglycemic effect, extract of fenugreek seed also displays neuroprotective properties (21) and anti-inflammatory effects (22,23) in disease animal models. These mechanisms of effects are consistent with the current trials of GLP-1 analogs in treatment of psoriasis (5) and Parkinson disease (2).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In addition to hypoglycemic effect, extract of fenugreek seed also displays neuroprotective properties (21) and anti-inflammatory effects (22,23) in disease animal models. These mechanisms of effects are consistent with the current trials of GLP-1 analogs in treatment of psoriasis (5) and Parkinson disease (2).…”
Section: Discussionsupporting
confidence: 75%
“…Mice with GLP-1R gene knock-out or with functionally deficient GLP-1R signaling exhibit impaired glucose homeostasis, learning, and memory (1). Clinical trials have also targeted GLP-1 signaling in other conditions, including psoriasis, heart disease, and neurodegenerative disease (2)(3)(4)(5). As such, GLP-1R signaling might be an ideal research target for the discovery and development of drugs for the treatment of various conditions from metabolic disorders to neurodegeneration.…”
mentioning
confidence: 99%
“…However, neurons expressing GLP-1Rs in notable areas, such as caudal hippocampus and the dopaminergic neurons in the substantia nigra, have no apparent innervations from GLP-1-producing neurons (1,3,14). Both areas are anatomic sites of deficient functions in disease that are ameliorable by GLP-1 analog therapy, which improves memory/learning in an Alzheimer mouse model and Parkinson symptoms in humans (5,6,41). It has been suggested that GLP1Rs in these areas might be activated by the circulating GLP-1 in cerebrospinal fluid and blood (40), which is normally at a level that is probably below the threshold concentration for GLP-1R activation (42).…”
Section: Discussionmentioning
confidence: 99%
“…Mice deficient in GLP-1R expression or with blunted GLP-1R function show impairment of physiologic features not limited to glucose homeostasis but also including learning and memory (4). Clinical trials targeting GLP-1 signaling to treat non-metabolic diseases include those for psoriasis, heart disease, and neurodegenerative diseases (5)(6)(7). Despite encouraging outcomes with GLP-1 analogs in reducing myocardial infarct size in acute coronary occlusion (7) and improving clinical symptoms in patients with Parkinson disease (5), the mechanisms of physiological regulation of GLP-1R signaling beyond energy homeostasis remain largely unknown.…”
mentioning
confidence: 99%
“…Nevertheless, the data provide 'strong encouragement' for assessing exenatide 'as a potential disease modifying agent in Parkinson's disease'. 10 'This is the first time in the 20 years I have lived with PD that I have witnessed such robust data that support the view that we can permanently alter the degenerative nature of Parkinson's,' Isaacs notes. 'The really exciting thing about exenatide is that it is approved for type 2 diabetes, and that means that, unlike other new medicines, it won't have to go through the same time-consuming and expensive safety procedures before it is able to be prescribed to people with PD.'…”
Section: Targeting Mitochondriamentioning
confidence: 89%